(3eaGJjM GdTQGFYs - (3GdcGTj Ch GdcGTGfj, , GdeJCdg GdMcje, eMSf Hf eQJVi Hf ajV Gddg eMehO, J(B1090(3g`s
(3ChdgG (B:s
(3HSe Gddg(B...(3GdMeO ddg GdPj gOGfG dOjf GdESdGe hSf dfG GdTQGFY hGdCMcGe HhSjdI fHjg GdeNJGQ(B...s
(3BNQgG (B:s
...(3gPG BNQ GdcdGe aj af GdYHGOGJ hGdSjGSGJ ef eaGJjM GdTQGFY hjJdhg af GdYHGOGJ hGdeYGedGJ(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B5(3,U(B290s
(3EjVGM Gdecfhf(B:(3L(B2(3,U(B521s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis